Cell Surface Display of Thermomyces lanuginosus Lipase in Pichia pastoris - Yang, Jiaming; Huang, Kui; Xu, Xiaomin; Miao, Yangli; Lin, Ying; Han, Shuangyan (Frontiers in Bioengineering and Biotechnology, 2020)
Thermomyces lanuginosus lipase (TLL) as a highly thermophilic, site-specific and highly selective enzyme, has the promising prospect of application in many fields: detergent, cosmetics and biochemical industry. Yeast surface display as a strategy to anchor proteins on the yeast cell wall, improves the stability of enzymes and thus reduces production costs. We constructed a novel cell surface display system, using cell wall anchor GCW61 from Pichia pastoris endogenous wall. By fusing GCW61 with the TLL2 NCBI Accession: O59952) that optimized codon synthesis, it can be displayed on the outer of the yeast cell wall. Flask fermentation was performed for 144 h with the enzyme activity up to 1964.76 U/g. Enzymatic characteristics of vacuum freeze-drying fermentation broth were characterized. The optimum substrate was p-nitrophenyl hexanoate. The whole-cell enzyme displayed the maximum activity at pH 9.0 and 55 °C and demonstrated characteristics of the high heat and alkaline pH resistance. Bivalent metal ions Ca2+, Mn2+, and Zn2+ ions had a strong activation effect on TLL2，while Cu2+, Fe2+, Fe3+, K+, Li+, Na+, and Co2+ had a sharp inhibitory effect on it. Our constructed TLL whole cell biocatalyst demonstrated simpler purified enzyme process than free enzyme and high enzyme activity, which is able to be further used in various applications.